Collective Dipole‐Dominated Doping of Monolayer MoS2: Orientation and Magnitude Control via the Supramolecular Approach. (12th July 2020) - Wang, Ye; Gali, Sai Manoj; Slassi, Amine; Beljonne, David; Samorì, Paolo
Abstract: Molecular doping is a powerful, tuneable, and versatile method to modify the electronic properties of 2D transition metal dichalcogenides (TMDCs). While electron transfer is an isotropic process, dipole‐induced doping is a collective phenomenon in which the orientation of the molecular dipoles interfaced to the 2D material is key to modulate and boost this electronic effect, despite it is not yet demonstrated. A novel method toward the molecular functionalization of monolayer MoS2 relying on the molecular self‐assembly of metal phthalocyanine and the orientation‐controlled coordination chemistry of axial ligands is reported here. It is demonstrated that the subtle variation of position and type of functional groups exposed on the pyridinic ligand, yields a molecular dipole with programed magnitude and orientation which is capable to strongly influence the opto‐electronic properties of monolayer MoS2 . In particular, experimental results revealed that both p‐ and n‐type doping can be achieved by modulating the charge carrier density up to 4.8 10 12 cm −2 . Density functional theory calculations showed that the doping mechanism is primarily resulting from the effect of dipole‐induced doping rather than charge transfer. The strategy to dope TMDCs is a highly modulable and robust, and it enables to enrich the functionality of 2D materials‐based devices for high‐performance applications in optoelectronics. Abstract : A novel approach to orientation controlled dipolar doping of MoS2 is demonstrated by exploiting functional axial ligands coordinated on self‐assembled supramolecular organic–inorganic heterostructures. Both n‐ or p‐type doping is achieved by modulating the charge carrier density up to 4.8 × 10 12 cm −2 . This collective doping effect is a powerful strategy to boost the performances of 2D materials for opto‐electronic applications.